Geochemical Negative Emissions Technologies: Part II. Roadmap - Maesano, Cara N.; Campbell, James S.; Foteinis, Spyros; Furey, Veronica; Hawrot, Olivia; Pike, Daniel; Aeschlimann, Silvan; Reginato, Paul L.; Goodwin, Daniel R.; Looger, Loren L.; Boyden, Edward S.; Renforth, Phil (Frontiers in Climate, 2022)
Geochemical negative emissions technologies (NETs) comprise a set of approaches to climate change mitigation that make use of alkaline minerals to remove and/or permanently store carbon dioxide (CO2) as solid carbonate minerals or dissolved ocean bicarbonate ions. This roadmap accompanies the comprehensive review of geochemical NETs by the same authors and offers guidance for the development and deployment of geochemical NETs at gigaton per year (Gt yr.−1) scale. We lay out needs and high-priority initiatives across six key elements required for the responsible and effective deployment of geochemical NETs: (i) technical readiness, (ii) social license, (iii) demand, (iv) supply chains, (v) human capital, and (vi) infrastructure. We put forward proposals for: specific initiatives to be undertaken; their approximate costs and timelines; and the roles that various actors could play in undertaking them. Our intent is to progress toward a working consensus among researchers, practitioners, and key players about initiatives that merit resourcing and action, primarily focusing on the near-term.